Die Reihenfolge der johanneischen Schriften - Schnelle, Udo (New Testament studies, 2011)
Usually, the three Johannine Letters are dated after the Gospel of John without extended discussion. The following essay will argue that all three Johannine letters were written before the Gospel of John marking the starting point of the Johannine line of tradition. Beside linguistic analyses two major arguments will be given: (1) 1 John is much more than simply an aid how to read the Gospel of John. 1 John establishes its own theological line of reasoning. It is necessary to understand that letter as a piece of theological thought on its own. Any dependence on the Gospel of John cannot be proved. (2) Dating 2 John and 3 John after the Gospel of John and 1 John needs to explain the far-reaching reduction of theology (and especially of Christology) in contrast to the other two Johannine writings. A convincing explanation for such a development has not been established until now. On the contrary, 2 John and 3 John represent the beginning of the development of Johannine theology., German abstract: Zumeist werden die drei Johannesbriefe summarisch im Anschluss an das Evangelium datiert. In diesem Aufsatz wird die These vertreten, dass die drei Johannesbriefe vor dem Johannesevangelium abgefasst wurden und den Anfang der johanneischen Traditionslinie bilden. Neben sprachlichen Beobachtungen werden dafür zwei Hauptargumente angeführt: (1) Der 1Joh ist weitaus mehr als eine Art ‘Lesehilfe’ zum Evangelium; er bildet eine eigene theologische Welt und muss zunächst aus sich selbst verstanden werden. Eine Abhängigkeit des 1Joh vom Evangelium lässt sich nicht nachweisen. (2) Wer den 2/3Joh nach dem Evangelium und dem 1Joh ansetzt, muss die umfassende Reduzierung jeder Form von Theologie (vor allem der Christologie) erklären. Eine solche Erklärung wurde bisher nicht erbracht. Vielmehr repräsentieren der 2/3Joh das Anfangsstadium der johanneischen Theologie.